THE NEW VIEW AT THE MANAGERIAL MODEL OF THE SOCIAL-ECONOMIC SYSTEM INNOVATIVE DEVELOPMENT - N. A. Kuz’Minykh (Russian Journal of Economics and Law, 2013)
Objective: to elaborate the managerial model of the social-economic system innovative development. Methods: scientific abstraction, comparison and analysis. Results: basing on the analysis of the Russian and foreign literature, the author specifies the categorical apparatus of innovative development. Within the frameworks of efficient management of the social-economic system innovative development, the rules, principles and approaches are proved, factors and conditions of innovative development are revealed. The managerial model of the social-economic system innovative development is proposed. Scientific novelty: elaboration of the managerial model of the social-economic system innovative development in the modern economy, based on the complex of the rules, principles, approaches, factors and conditions of innovative development, allowing to make efficient managerial decisions of innovative character. Practical value: possibility to use the research results for efficient management and forming the innovative development strategy in various social-economic systems.